Role of the banking sector in sustainable economic development – The case of Azerbaijan - Ayaz, Museyibov; Yusif, Mammadov; Joshgun, Jafarov (Dunakavics, 2024)
This study examines the role of the banking sector in Azerbaijan's economic development, focusing on its impact on credit expansion, GDP growth, and sectoral financial dynamics. The banking sector is crucial for financing small and medium-sized enterprises (SMEs), driving economic growth, and enhancing productivity through increased employment and investment. The study employs a panel VAR model to explore the relationship between regulatory capital, credit extension, and economic growth, highlighting how regulatory capital impacts loan-to-deposit ratios and GDP growth. Data from 2005 to 2022 indicates a strong positive correlation between bank loans and GDP growth, though the effect varies by loan size and capital regulation policies. The analysis reveals that bank loans and deposits significantly influence GDP, with deposits showing a stronger correlation. Despite improvements in the financial sector, including reforms and infrastructure modernization, Azerbaijan's banking system faces challenges in credit allocation and financial depth compared to regional and global benchmarks. The study identifies that a substantial portion of loans is directed towards households rather than productive sectors, impacting overall economic growth. Key sectors such as agriculture and manufacturing have seen decreased loan shares, affecting their development. The findings suggest a need for enhanced regulatory frameworks, better risk management, and targeted financial policies to improve sectoral credit distribution and support sustainable economic growth in Azerbaijan.